1973
DOI: 10.1016/0003-9969(73)90109-x
|View full text |Cite
|
Sign up to set email alerts
|

A selective medium for Streptococcus mutans

Abstract: Summary-A selective medium was developed for the isolation of Streptococcus mutans from human dental plaque. Mitis-salivarius agar was modified by adding 0.2 units/ml bacitracin and by increasing the sucrose concentration to 20 per cent. At these concentrations, the selective agents allowed the undiminished recovery of Strep. mutans with maximum inhibition of the balance of the streptococcal flora normally encountered on this medium. Enterococci or yeasts were sometimes observed upon direct culturing of plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
507
0
20

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 869 publications
(531 citation statements)
references
References 15 publications
4
507
0
20
Order By: Relevance
“…However, our study showed no statistically significant difference between the two groups. These results correlated with that of Zichert [17] and Ogaard [4] who in their study found that there was no difference in the caries activity between male and female patients.…”
Section: Statistical Analysis and Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, our study showed no statistically significant difference between the two groups. These results correlated with that of Zichert [17] and Ogaard [4] who in their study found that there was no difference in the caries activity between male and female patients.…”
Section: Statistical Analysis and Resultssupporting
confidence: 89%
“…However, the scanning electron microscopy (SEM) used in his technique does not carry much advantage compared to our study design as SEM technique too lacks the ability to identify species [17] and also it did not analyse the bacteria clinging to all sides of the elastomeric rings. Our study had the advantage that accounted all the dispersed bacteria into the solution for calculation and also was cost effective when compared to SEM study.…”
Section: Statistical Analysis and Resultsmentioning
confidence: 99%
“…One millilitre of the saliva was transferred to 19 to estimate the number of MS, and on Rogosa SL agar to estimate the number of LB. The MSB agar plates were incubated in 95% N 2 and 5% CO 2 at 378C for 2 days and the SL agar plates were incubated aerobically at 378C for 3 days.…”
Section: Saliva Sampling and Bacteria Cultivationmentioning
confidence: 99%
“…In addition, dental biofilm samples from the cervical third of the buccal surface of the first maxillary premolars, adjacent to the bracket, were collected to confirm the presence of S. mutans. The collection was performed using a plastic curette (Jon, São Paulo, SP, Brazil) and S. mutans quantification was checked using Mitis Salivarius Bacitracin (MSB) agar, which is selective for S. mutans (18,19).…”
Section: Sample Selectionmentioning
confidence: 99%